Seasonal characteristics of CO2 fluxes in a rain-fed wheat field ecosystem at the Loess Plateau - Q. Guo; W. W. Li; D. D. Liu; W. Wu; Y. Liu; X. X. Wen; Y. C. Liao (Spanish Journal of Agricultural Research, 2013)
This study investigated the dynamics of CO2 flux in a rain-fed wheat field ecosystem using an eddy covariance technique during the 2011 to 2012 wheat-growing season at the Loess Plateau, China. Results showed that the daily CO2 flux was closely related to photosynthetically active radiation (PAR), growth stage, soil temperature and rainfall. The average CO2 flux at different growth stages followed the order jointing and booting > erecting > reviving > heading > wintering > seeding and tillering > grain filling > ripening. The first four stages were carbon sinks, whereas the last four stages were carbon sources. The relationship between nighttime CO2 flux and air temperature was significant and fitted the index model (y=aebt). The relationship between daytime CO2 flux and PAR was also significant and fitted the quadratic model (y=ax2+bx+c). Moreover, daytime CO2 flux was significantly correlated with air temperature and PAR at the erecting, jointing and booting, and heading stages. Nighttime CO2 flux was also significantly correlated with soil temperature at 5 cm depth at the heading as well as jointing and booting stages. The carbon budget in the rain-fed wheat ecosystem was -401 g C m-2 yr-1, which was higher than those in other wheat ecosystems. This study implies that the ability of carbon-sequestration in different wheat field ecosystems may respond differently to climate and environment change.